Automatic Fire Detector using Arduino with Output Evacuation Route via Short Message Service (SMS) and Warning via Ringtones - Margaretha Palma Puspita; Bheta Agus Wardijono (Universitas Islam Sumatera Utara, 2021)
In this modern era, the use of electricity is increasing and of course it is very prone to trigger fires. When there is a fire, many people are trapped and difficult to find an evacuation route if it is in a difficult range such as in a tall building. In this final project aims to provide fire warnings and display safe routes as evacuation routes. This fire detection device uses Arduino Uno as a controller and LM35 temperature sensor as a fire detector. GSM Shield is used to send SMS and make calls to the user. The working principle of this tool, by detecting the presence of a fire and the input of the heat temperature is processed when the conversion voltage is 350mV in accordance with the provisions of the fire status. The process is run by the program that has been uploaded to Arduino, after the process is run, then the output appears in the form of fire information and evacuation route with SMS and fire alerts with ringtones. There are 6 temperature sensors used, with 2 sensors installed on each floor. Each sensor that detects a fire, an SMS is sent with the specified status of each sensor and the safe route that must be passed. After the SMS is sent, the phone call comes to alert the user if they do not know of a fire or have not seen the incoming SMS.